2020
DOI: 10.1021/jacs.0c01092
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Forming Early Intermediate Structures Dictate the Pathway of Capsid Assembly

Abstract: There are ∼ 10 30 possible intermediates on the assembly path from hepatitis B capsid protein dimers to the 120-dimer capsid. If every intermediate was tested, assembly would often get stuck in an entropic trap and essentially every capsid would follow a unique assembly path. Yet, capsids assemble rapidly with minimal trapped intermediates, a realization of the Levinthal paradox. To understand the fundamental mechanisms of capsid assembly it is critical to resolve the early stages of the reaction. We have used… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
90
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(100 citation statements)
references
References 70 publications
8
90
2
Order By: Relevance
“…Our results complement the recent study by Asor et al ( 34 , 44 ), which examined the assembly of empty HBV capsids for assembly domain dimers using time-resolved small-angle x-ray scattering (SAXS). The SAXS experiments used much higher protein concentrations than HS-AFM to obtain an interpretable signal at a resolution that allowed distinguishing intermediates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results complement the recent study by Asor et al ( 34 , 44 ), which examined the assembly of empty HBV capsids for assembly domain dimers using time-resolved small-angle x-ray scattering (SAXS). The SAXS experiments used much higher protein concentrations than HS-AFM to obtain an interpretable signal at a resolution that allowed distinguishing intermediates.…”
Section: Discussionsupporting
confidence: 88%
“…Our results indicate that the diamond-shape pentameric arrangement of Cps is a critical participant in HBV assembly, as a minimal stable structure of Cps able to condense single-stranded nucleic acids. Previous studies have reported the accumulation of small HBV assembly intermediates for truncated versions of Cp (without the CTD) and in the absence of nucleic acids ( 34 , 40 , 42 44 ). The assembly model proposed here ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The HBV capsid is composed of 120 core protein (Cp) dimers that primarily assemble to form capsids with T = 4 icosahedral symmetry (~95%), with a small number of T = 3 capsids having been observed in HBV-infected human liver samples and in vitro-assembled capsids from recombinant HBV Cp [ 7 , 8 , 9 , 10 ]. HBV genome synthesis from pgRNA via reverse transcription is highly dependent on properly assembled viral capsids [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although capsid assembly has nucleation and elongation phases, there are no discrete stopping points for manipulation and modification of specific intermediates 27 29 . Here we used Hepatitis B Virus (HBV) capsid assembly as a model system and demonstrated an effective approach to break the spontaneous assembly into addressable steps 28 , 30 , 31 . HBV capsid dimeric subunits can assemble two species of capsids, T = 3 capsid with 90 dimers and T = 4 capsid with 120 dimers.…”
Section: Introductionmentioning
confidence: 99%